HIGH SCHOOL PRINCIPAL'S STRATEGY IN IMPROVING THE QUALITY OF EDUCATION IN ERA 4.0 - Asnawati, Asnawati (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to identify and analyze the strategies used by high school principals in improving the quality of education in the 4.0 era. Education in the era of Industrial Revolution 4.0 demands paradigm changes and innovative strategies in facing the challenges of the times. High school principals have a crucial role in improving the quality of education so that it is relevant and responsive to the needs of today's students and able to produce graduates who are ready to face future challenges. This research uses a qualitative approach with descriptive methods. Data collection techniques are carried out through observation, interviews and documentation studies. The data analysis procedures are Data Redaction, Data Presentation, and Verification. Meanwhile, the research subjects were high school principals, deputy principals and teachers. The place of research was carried out at Badridduja Superior High School Jl. Sunan Kudus no 02 Kraksaan Wetan Kraksaan Probolinggo. The results of the research show that: (1) High school principals in improving the quality of education first plan a program by detailing the needs of educators and education staff who will carry out their duties, plan the curriculum that will be implemented, plan policies for adding subjects; (2) Create an organizational structure that involves parents through high school committees and completes the necessary infrastructure; (3) Providing a good and calm example at work, motivating and rewarding personnel both morally and materially, increasing welfare, involving educators and education staff in training and motivating senior teachers to have the spirit of life long education; (4) supervise output and students from the admissions process until completion at the high school. (5) The obstacles experienced are the presence of teachers who are still undisciplined, lack of communication between high school principals and some teachers.